Status needs and problems of physical education in the public elementary schoools of Tuguegarao - Espiritu, Agripina (Garcia) 1924- ([Quezon City s.n.], 1971)
This study shows that the major purposes of Physical education which consist of the building up of physical fitness, achieving social maturity, and meeting with satisfaction the problems of leisure time, were neglected. It investigates the status, needs, and problems in Physical Education of public elementary schools in Tuguegarao which covers the two districts, District I and District II, in the Division of Cagayan I.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Physical education and training -- Philippines -- Tuguegarao, Cagayan